2-Methylthio-N7-methyl-cis-zeatin, a new antimalarial natural product isolated from a Streptomyces culture. Issue 1 (3rd November 2021) - Lopez, Julius Adam V; Nogawa, Toshihiko; Yoshida, Kazuko; Futamura, Yushi; Osada, Hiroyuki
ABSTRACT: 2-Methylthio- N 7 -methyl- cis- zeatin (1 ) was isolated from the culture broth of Streptomyces sp. 80H647 along with 2 known purine derivatives, 5′-methylthioinosine (2 ) and AT-265 (dealanylascamycin, 3 ). The structure elucidation of compound 1 was accomplished by high-resolution mass spectrometry (HRMS) and nuclear magnetic resonance (NMR) analyses. It inhibited the growth of Plasmodium falciparum 3D7 with a GI50 of 2.4 µm and had no effect on the growth of Arabidopsis at 2 µm . This is the first report of an N 7 -methylated zeatin-type natural product from Streptomyces and as an antimalarial compound. Graphical Abstract: